Proposal for an experimental-numerical method for friction description in sheet metal forming - Trzepieciński, Tomasz (Strojniški vestnik, 2015)
During the forming of draw pieces with complex shapes, such as car bodies, it is necessary to use dies with varying outline curvatures and varying radii of edge fillets. In such conditions, using the cylindrical counter-samples for friction modelling on the die fillet surface does not fully reflect the friction conditions on the edge of the die. In this article, a proposal for an experimental numerical method of friction determination on the rounded profiles of punch edges is presented. The method involves a bending under tension (BUT) test that is devised to simulate the frictional conditions over the punch radii. Numerical simulations of BUT tests were conducted with ABAQUS software. An elastic-plastic approach with Hill's (1948) anisotropic material formulation and isotropic strain hardening were considered. Results of both experimental and numerical approaches confirmed the usefulness of the proposed method.
Keywords: finite element method; koeficient trenja; metoda končnih elementov; preizkus BUT; preoblikovanje pločevine; trenje; upogibanje pod napetostjo